(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Preschool age is one of the most important periods in the life of every child, during which there is a development of figurative forms of cognition of reality — perception, imaginative thinking and imagination. The child becomes ready to study and master knowledge about the world around him. Children are active in various types of activities, such as play, work, study, and also the child has independent play activities.